Development of a robust chromatographic method for the detection of chlorophenols in cork oak forest soils. - McLellan, Iain; Hursthouse, Andrew; Morrison, Calum; Varela, Adélia; Pereira, Cristina Silva (Environmental monitoring and assessment, 2014)
A major concern for the cork and wine industry is 'cork taint' which is associated with chloroanisoles, the microbial degradation metabolites of chlorophenols. The use of chlorophenolic compounds as pesticides within cork forests was prohibited in 1993 in the European Union (EU) following the introduction of industry guidance. However, cork produced outside the EU is still thought to be affected and simple, robust methods for chlorophenol analysis are required for wider environmental assessment by industry and local environmental regulators. Soil samples were collected from three common-use forests in Tunisia and from one privately owned forest in Sardinia, providing examples of varied management practice and degree of human intervention. These provided challenge samples for the optimisation of a HPLC-UV detection method. It produced recoveries consistently >75 % against a soil CRM (ERM-CC008) for pentachlorophenol. The optimised method, with ultraviolet (diode array) detection is able to separate and quantify 16 different chlorophenols at field concentrations greater than the limits of detection ranging from 6.5 to 191.3 μg/kg (dry weight). Application to a range of field samples demonstrated the absence of widespread contamination in forest soils at sites sampled in Sardinia and Tunisia.
Keywords: chlorophenols; Cork oak; hplc; method development; NATO Science for peace; Quercus Suber L; soils

Suberin isolation from cork using ionic liquids: characterisation of ensuing products - Ferreira, Rui; Garcia, Helga; Sousa, Andreia F.; Petkovic, Marija; Lamosa, Pedro; Freire, Carmen S. R.; Silvestre, Armando J. D.; Rebelo, Luís Paulo N. Luis Paulo N.; Pereira, Cristina Silva (New Journal of Chemistry, 2012)
Cholinium alkanoates, a class of benign ionic liquids, were demonstrated to efficiently extract suberin domains from cork. A detailed characterisation of the extracted material has yet to be attained. In the present study the significance of the alkylic chain length of the anion and the ionic liquid's basicity was investigated. The results obtained emphasise cholinium hexanoate's selection; it proved to be a straightforward process, also ensuring the recyclability and reusability of the ionic liquid. The extracted suberinic material has been thoroughly characterised for the first time by ATR-FTIR, NMR, GC-MS and thermal analyses. Data showed that it is mainly composed of oligomeric or polymeric aliphatic esterified structures, resulting from suberin partial cleavage. More than 40 wt% of the extracted suberinic material was found to be cross-linked. Even though, the composing monomeric units were similar to those usually identified in suberin samples obtained by the conventional extraction processes. These data pave the way for advanced studies of suberin monomers/oligomers as building-blocks for the development of novel biopolymers and biomaterials.
The following values have no corresponding Zotero field: publisher: The Royal Society of Chemistry
Keywords: Cholinium alkanoates; Cork; Extraction; suberin; suberinic materials (voyant)